Empowering SMKS Nusantara Banyuwangi Students through Canva Training to Improve Graphic Design Skills - Aprilia, Defi Nurdiana; Setiawan, Donny; Farhanto, Galih (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Currently, the development of design technology is increasing. Graphic design is a crucial skill in today's digital era. The rapid growth of definitive design technology greatly influences community activities, especially among vocational school students. Canva is a graphic design application that is popular and easy to use. This research aims to determine the effectiveness of Canva training in improving the graphic design skills of SMKS Nusantara Banyuwangi students and to increase student's knowledge and experience regarding the use of the Canva application for SMKS Nusantara Banyuwangi students. This training uses a workshop method with a participatory approach and individual communication. This Canva training is specifically for students, where in this training, students create a motivational slogan and a poetry poster. Canva training shows high enthusiasm from students. This can be seen from the number of students who want to immediately apply the training results by making posters. Apart from that, this Canva graphic design training produces sound output for participants..